Effect of Light on Expression of Clock Genes in Xenopus laevis Melanophores. (18th January 2014) - Magalhães Moraes, Maria Nathália de Carvalho; de, Maristela; Ribeiro Ramos, Bruno Cesar; de, Leonardo Henrique Ribeiro Graciani; de, Ana Maria
Abstract Light–dark cycles are considered important cues to entrain biological clocks. A feedback loop of clock gene transcription and translation is the molecular basis underlying the mechanism of both central and peripheral clocks. Xenopus laevis embryonic melanophores respond to light with melanin granule dispersion, response possibly mediated by the photopigment melanopsin. To test whether light modulates clock gene expression in Xenopus melanophores, we used qPCR to evaluate the relative mRNA levels of Per1, Per2, Clock and Bmal1 in cultured melanophores exposed to light–dark (LD) cycle or constant darkness (DD). LD cycles elicited temporal changes in the expression of Per1, Per2 and Bmal1. A 10‐min pulse of blue light was able to increases the expression of Per1 and Per2. Red light had no effect on the expression of these clock genes. These data suggest the participation of a blue‐wavelength sensitive pigment in the light–dark cycle‐mediated oscillation of the endogenous clock. Our results add an important contribution to the emerging field of peripheral clocks, which in nonmammalian vertebrates have been mostly studied in Drosophila and Danio rerio. Within this context, we show that X. laevis melanophores, which have already led to melanopsin discovery, represent an ideal model to understanding circadian rhythms.